Peran Pembiayaan Syariah Dalam Mendorong Pemberdayaan UMKM: Studi Kasus Lembaga Keuangan Mikro Syariah Di Indonesia - Susana, Lina Marlina; Rizky Muhammad.F; Alim, Aji Nur; Aminudin, Mizan (Ekonosfera: Jurnal Ekonomi, Akuntansi, Manajemen, Bisnis dan Teknik Global, 2025)
This study discusses the role of Islamic financing in empowering Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, which play an important role in the national economy through job creation and reducing economic inequality. This research aims to explore the impact of sharia-based financing offered by Islamic Microfinance Institutions (MFIs) and Islamic banks in supporting MSMEs, particularly through financing products such as murabahah, musyarakah, and mudharabah. Using a qualitative approach and secondary data analysis, this study collected data from journals, books, and statistical sources to identify key themes in MSME empowerment through Islamic finance. The results show that Islamic finance supports the growth of MSMEs by providing fairer and more sustainable access to funding, as well as through mentoring programmes that improve the managerial capabilities of MSMEs. Despite challenges such as low Islamic financial literacy, this study concludes that Islamic financing has great potential in strengthening the contribution of MSMEs to the national economy.